The asthma‐rhinitis multimorbidity is associated with IgE polysensitization in adolescents and adults. Issue 7 (6th February 2018) - Siroux, V.; Ballardini, N.; Soler, M.; Lupinek, C.; Boudier, A.; Pin, I.; Just, J.; Nadif, R.; Anto, J. M.; Melen, E.; Valenta, R.; Wickman, M.; et al.
Abstract: Background: Children with multimorbid asthma and rhinitis show IgE polysensitization to several allergen sources. This association remains poorly studied in adolescents and adults using defined allergen molecules. We investigated IgE sensitization patterns towards a broad panel of aeroallergen components in adults and adolescents with a focus on individuals with asthma and rhinitis multimorbidity. Methods: IgE reactivity to 64 micro‐arrayed aeroallergen molecules was determined with the MeDALL‐chip in samples from the French EGEA study (n = 840, age = 40.7 ± 17.1) and the Swedish population‐based birth cohort BAMSE (n = 786, age = 16 ± 0.26). The age‐ and sex‐adjusted associations between the number of IgE‐reactive allergen molecules (≥0.3 ISU) and the asthma‐rhinitis phenotypes were assessed using a negative binomial model. Results: Groups representing 4 phenotypes were identified: no asthma‐no rhinitis (A−R−; 30% in EGEA and 54% in BAMSE), asthma alone (A+R−; 11% and 8%), rhinitis alone (A−R+; 15% and 24%) and asthma‐rhinitis (A+R+; 44% and 14%). The numbers of IgE‐reactive aeroallergen molecules significantly differed between phenotypes (median in A−R−, A+R−, A−R+ and A+R+: 0, 1, 2 and 7 in EGEA and 0, 0, 3 and 5 in BAMSE). As compared to A−R− subjects, the adjusted ratio of the mean number of IgE‐reactive molecules was higher in A+R+ than in A+R− or A−R+ (10.0, 5.4 and 5.0 in EGEA and 7.2, 0.7 and 4.8 in BAMSE). Conclusion: The A+R+ phenotype combined the sensitization pattern of both the A−R+ and A+R− phenotypes. This multimorbid polysensitized phenotype seems to be generalizable to various ages and allergenic environments and may be associated with specific mechanisms.